Efforts to Improve Cognitive Learning Outcomes of High School Physics Students Through the Application of Inquiry Learning Models - Anisa Nadila; Donna Sitompul; Rizka Carnelia Putri (Institute of Educational, Research, and Community Service, 2023)
The inquiry approach is one of the approaches that can be applied to learning Physics in high school. Inquiry is a discovery approach, but it is different from the discovery approach. Inquiry emphasizes more on searching. Inquiry requires students to become researchers or scientists, but in the context of learning, students are still guided by the teacher, therefore inquiry is said to be a guided discovery approach. Inquiry can be carried out through several systematic steps, namely: 1) Formulate a problem; 2) Propose hypotheses; 3) Collect data; 4) Test hypotheses based on data collected; and 5) Make conclusions. Applying the inquiry approach in mathematics learning can help students learn to find the origin of a formula, concept, or theory in physics. The main targets of inquiry learning activities are (1) maximum student involvement in the process of learning activities; (2) the direction of activities logically and systematically on learning objectives; and (3) developing an attitude of trust in students about what is found in the inquiry process.